Tradisi Hiziban sebagai Momentum Meningkatkan Karakteristik Al Washatiyyah dan Merealisasikan Islah bagi Penerus Perjuangan Maulana Syaikh - Abdul Rahman (MANAZHIM, 2023)
The objectives of this study are: 1) To understand how the Hiziban tradition can serve as a momentum to enhance the characteristics of Al Washatiyyah and contribute to the realization of Islah in the personal and social lives of the successors of Maulana Syaikh's struggle; 2) To explore the relationship between the Hiziban tradition, the characteristics of Al Washatiyyah, and Islah in the context of Maulana Syaikh's struggle; 3) To identify the perspectives, experiences, and challenges faced by individuals involved in the Hiziban tradition regarding the enhancement of Al Washatiyyah characteristics and efforts in Islah as the successors of Maulana Syaikh's struggle. This research employs a qualitative descriptive method with a phenomenological approach. The study was conducted in Lombok, West Nusa Tenggara, with a sample of Hiziban congregants. Data collection techniques include in-depth interviews, participatory observation, documentation, and document analysis. The research validity and reliability are ensured through data triangulation, researcher reflection, and participant feedback. Data analysis is conducted using a thematic analysis approach. The findings of this study are as follows: 1) The Hiziban tradition can serve as a momentum to enhance the characteristics of Al Washatiyyah and contribute to the realization of Islah in the personal and social lives of the successors of Maulana Syaikh's struggle through several mechanisms and aspects, namely: worship and remembrance practices, the formation of quality communities, education and teaching, and social empowerment and well-being; 2) The relationship between the Hiziban tradition, the characteristics of Al Washatiyyah, and Islah in the context of Maulana Syaikh's struggle is interconnected and mutually influential. The Hiziban tradition plays a role as a momentum that strengthens the characteristics of Al Washatiyyah and contributes to the realization of Islah in the context of Maulana Syaikh's struggle; 3) Individuals involved in the Hiziban tradition have positive perspectives on spiritual values and practices, profound experiences in these practices, but also face challenges in maintaining consistency, motivation, and overcoming negative perceptions from the surrounding community. Awareness of these challenges can help individuals design appropriate strategies to overcome obstacles and continue to develop themselves in the journey of enhancing the characteristics of Al Washatiyyah and efforts in Islah.